Plant invasion and naturalization are influenced by genome size, ecology and economic use globally - Guo, Kun; Pyšek, Petr; van Kleunen, Mark; Kinlock, Nicole L; Lučanová, Magdalena; Leitch, Ilia J; Pierce, Simon; Dawson, Wayne; Essl, Franz; Kreft, Holger; Lenzner, Bernd; Pergl, Jan; et al. (Nature communications, 2024)
Human factors and plant characteristics are important drivers of plant invasions, which threaten ecosystem integrity, biodiversity and human well-being. However, while previous studies often examined a limited number of factors or focused on a specific invasion stage (e.g., naturalization) for specific regions, a multi-factor and multi-stage analysis at the global scale is lacking. Here, we employ a multi-level framework to investigate the interplay between plant characteristics (genome size, Grime's adaptive CSR-strategies and native range size) and economic use and how these factors collectively affect plant naturalization and invasion success worldwide. While our findings derived from structural equation models highlight the substantial contribution of human assistance in both the naturalization and spread of invasive plants, we also uncovered the pivotal role of species' adaptive strategies among the factors studied, and the significantly varying influence of these factors across invasion stages. We further revealed that the effects of genome size on plant invasions were partially mediated by species adaptive strategies and native range size. Our study provides insights into the complex and dynamic process of plant invasions and identifies its key drivers worldwide.
Keywords: Humans; Introduced Species; státní občanství; ekosystém; ekologie; Citizenship; zavlečené druhy; Plants; délka genomu; Genome Size; Biodiversity; biodiverzita; Ecology; Ecosystem; lidé; rostliny